It's all about tax rates: An empirical study of tax perception - Kay Blaufus; Jonathan Bob; Jochen Hundsdoerfer; Dirk Kiesewetter; Joachim Weimann (Arbeitskreis Quantitative Steuerlehre (arqus), 2010)
In this paper we apply conjoint analysis to study the influence of changes in the tax rate and the tax base on the perceived tax burden. Our results show that the majority of individuals do not make rational tax decisions based on the actual tax burden, but rather use simple decision heuristics. This leads to the importance of the tax rate being significantly overestimated and the importance of the tax base being significantly underestimated. Furthermore we determine framing effects and show that under specific assumptions, a rise in the actual tax burden can lead to a electoral success.
Keywords: D03; G11; H20; H30; K34; M41; 330; behavioral public finance; decision heuristics; framing effects; perceived tax burden; tax-cut-cum-base-broadening; tax complexity; tax illusion; Steuerbelastung; Wahrnehmung; Steuertarif; Steuermoral; Framing; Conjoint-Analyse; Deutschland